Variation in infection rates of blue-stain, mould and white rot tropical fungi on mixed light Malaysian woods - Wong, Andrew H.H; Sabri, Ahmad (IRGWP, 2000)
The modified 3-week FRIM laboratory method for screening of anti-sapstain formulations against three representative tropical fungi causing blue-stain (Botryodiplodia theobromae), mould (Paecilomyces variotii) and white rot (Schizophyllum commune) infection of sapwood species was used to examine the relative resistance of the sapwood of eight mixed light Malaysian woods, Scots pine (Pinus sylvestris), medium density fibreboard produced from Rubberwood (Hevea brasiliensis) and the heartwood of Sentang (Azadirachta excelsa), to infection by these organisms. After 21 days it was found that Ramin (Gonystylus spp.), Rubberwood, Mersawa (Anisoptera sp.), Ludai (Sapium spp.), Yellow meranti (Shorea spp.), Scots pine and Jelutong (Dyera costulata) were highly susceptible to the pooled combinations of bluestain, mould or white rot infection often sustaining >50% overall mean fungal coverage or when at least one of the infection types has reached maximum mean coverage (75.5%) of the wood samples. However, the Rubberwood-based fibreboard, and particularly Sentang, and the softwood Agathis spp. from Kelantan (trade name: Damar minyak) and Sarawak (trade name: Bindang), were relatively moderately susceptible to infection, sustaining between 9 and 47% overall mean fungal coverage after 21 days, or even considerably less susceptible (5 – 20% overall coverage) after 14 days. There was absence of both blue-stain and white rot fungal growth on all samples dipped in a low (0.03%/0.03%) fungicide concentration of a MBT/TCMTB anti-sapstain formulation. Such laboratory test results could have significant implications to field or industrial sapstain control of sapwood timbers concerning the lag time between tree felling and anti-sapstain treatment and seasoning.